Targeting CRTC2 reverses STK11 mutant NSCLC tumor resistance to immunotherapy - Dimitri Robay; Ole Ackermann; Laurent Laborde; Xingyi Shi; Federico Oreglia; Ramona Stump; Sabina Ciaghi; Giorgio G. Galli; Laura Holzer; Lorraine Villemin; Joel Wagner; Jincheng Wu; et al. (Proceedings of the National Academy of Sciences, 2026)
Non–small cell lung cancer (NSCLC) patients with tumors harboring STK11 mutations are resistant to standard of care anti-PD-1/PD-L1 blockade. For this patient population there are no currently available tailored treatments, underlying the critical need to discover effective therapeutic strategies. In this study, we dissected the molecular mechanisms responsible for STK11 -mediated resistance to immune checkpoint blockade (ICB) and identified CRTC2, a coactivator of the transcription factor cAMP response element-binding protein (CREB), as a key signaling node regulating Stk11 -dependent cell-extrinsic functions. CRTC2 deletion remodeled the immune profiles of Stk11 -KO tumors and resensitized them to anti-PD-1 treatment, comparably to Stk11 -proficient tumors. Mechanistically, the abrogation of the binding between CRTC2 and CREB was sufficient to restore sensitivity to immunotherapy. These findings provide critical insights into the central role of CRTC2 in modulating response to ICB and identify the disruption of CRTC2–CREB interaction as a potential therapeutic approach for this patient population.